The analysis and comparison of Pilicz’s test results as an evaluation of the physical fitness - Chmiel, Justyna; Chołuj, Kamil; Fijewski, Adam; Majcher, Piotr (Polish Journal of Public Health, 2011)
Introduction. A negative effect of civilization changes is lowering of the level of individual physical fitness and more and more frequent phenomenon of hypokinesis. Aim. The aim of the study is to compare the results of the tests conducted in the group of the 1st and 2nd year pharmacy students in 1990/92, 1999/01 and 2007/08. Additionally, the study attempts at anticipating the direction of students’ physical development changes. Materials and methods. The research was conducted in a group of 90 female pharmacy students of the Medical University of Lublin. The study focused on testing motor skills with the use of motor skills test by Stefan Pilicz which was supplemented with the stamina test by Denisiuk. Results. Grades ranging from 4(B) to 5(A) constituted 70% of all the grades in 1990/1992; in 1999/01 they constituted 51%, and in 2007/08 – only 37%. The best results were achieved by the 1990/92 test group with the average grade of 4.0; the 1999/01 group obtained the average grade of 3.75; the 2007/2008 – test group was classified as the weakest with the average result of 3.5. Discussion. The observed decline in the level of physical fitness of the female pharmacy students at the Medical University of Lublin may be caused by the immense civilization development (communication, automotive boom), life in constant haste and stress, poor diet (fast food) and a low level of students’ physical activity. Conclusion. Even though the general level of the students’ motor skill is in decline, physical fitness of the students improves as a result of their participation in physical education classes.